FOLLOWING THE RULES? A MIXED MESSAGE FROM INDONESIA - Setyadi, Agus; Rusmin,; Brown, Alistair; Tower, Greg (The journal of contemporary issues in business and government, 2007)
This study examines Indonesian Accounting Regulatory Compliance (IARC) by analysing companies' financial reports. Agency theory offers insights into the tendency of listed companies to follow the rules particularly to better ascertain whether or not differing ownership and governance structures lead to increased compliance. Analysis reveals a surprisingly low level of only 43 percent compliance with accounting rules. T- test and statistical regression analysis show that industry type (p-value of 0.013) and auditor type (0.036) are significant predictors of IARC. The level of average compliance is significantly lower than the 88 percent compliance findings of a similar study by Tower, Hancock and Taplin (1999) for other Asian countries. The fundamental implication of the study is that much more regulatory intervention is needed. These findings add to the growing number of studies expressing concern about the issue of lack of effective supervision and sanctions in Indonesia's regulatory compliance (World Bank, 2005).